Women's Murder Club : 4th of July - Patterson, James 1947-; Paetro, Maxine; McCormick, Carolyn; Thomsen, Kevin (New York : Hachette Audio, 2005)
After losing one of its own, Lindsay Boxer and the Women's Murder Club make a courageous return for their fourth and most chilling case ever--one that could easily be their last. A young girl is killed in crossfire after a routine arrest goes terribly wrong, and Lt. Lindsay Boxer has to defend herself against a charge of police brutality. In a landmark trial that transfixes the nation, Lindsay fights to save her career and her sanity. While awaiting trial, Lindsay escapes to the beautiful town of Half Moon Bay, but the peaceful community there is reeling from a string of unspeakable murders. Working with her friends in the Women's Murder Club, Lindsay finds a link between these killings and a case she worked on years before--an unsolved murder that has haunted her ever since.
Compact disc.
Unabridged.
Packaging elements copyright 2008.
Produced and directed by Kevin Thomsen.
Read by Carolyn McCormick.
Keywords: Policewomen -- Fiction; Female friendship -- Fiction; Serial murders -- Fiction; Police shootings -- Fiction; Police -- Fiction -- California; Trials (Police misconduct) -- Fiction; Women detectives -- Fiction -- California; Audiobooks; Half Moon Bay (Calif.) -- Fiction; Mystery fiction; Audiobooks